Are We Preparing the Next Generation of Fisheries Professionals to Succeed in their Careers?: A Survey of AFS Members. Issue 8 (2nd August 2016) - McMullin, Steve L.; DiCenzo, Vic; Essig, Ron; Bonds, Craig; DeBruyne, Robin L.; Kaemingk, Mark A.; Mather, Martha E.; Myrick, Christopher; Phelps, Quinton E.; Sutton, Trent M.; Triplett, James R.
Abstract : Natural resource professionals have frequently criticized universities for poorly preparing graduates to succeed in their jobs. We surveyed members of the American Fisheries Society to determine which job skills and knowledge of academic topics employers, students, and university faculty members deemed most important to early‐career success of fisheries professionals. Respondents also rated proficiency of recently hired, entry‐level professionals (employers) on how well their programs prepared them for career success (students and faculty) in those same job skills and academic topics. Critical thinking and written and oral communication skills topped the list of important skills and academic topics. Employers perceived recent entry‐level hires to be less well‐prepared to succeed in their careers than either university faculty or students. Entry‐level hires with post‐graduate degrees rated higher in proficiency for highly important skills and knowledge than those with bachelor's degrees. We conclude that although universities have the primary responsibility for developing critical thinking and basic communication skills of students, employers have equal or greater responsibility for enhancing skills of employees in teamwork, field techniques, and communicating with stakeholders. The American Fisheries Society can significantly contribute to the preparation of young fisheries professionals by providing opportunities for continuing education and networking with peers at professional conferences.